Bulgaria Country Report - Smilov, Daniel (2000)
The 1991 Constitution of the Republic of Bulgaria proclaimed the principle of people's sovereignty in Article 1(2): "the whole power of the state stems from the people. It is exercised by the people directly, and through the bodies envisaged by the Constitution". However, the constitutional practice developed in the country, and the laws adopted since 1991, have rendered the direct forms of democracy largely inoperative, especially at the national level. The forms of direct democracy have been diminished to an instrument of party politics, an instrument, which, for the last ten years, has fallen into disuse. Direct democracy cannot be, even theoretically, an effective check to representative democracy in Bulgaria, because the adopted legislation on national referenda and plebiscites allows for the representative bodies of state power to determine both the subject-matter and the timing of any national popular vote: in fact, they have an effective veto on every proposal for referendum. In what follows I will discuss the legal arrangements envisaged by these documents as well as the practices in the sphere of direct democracy developed in Bulgaria since 1989.